2017
DOI: 10.15761/imm.1000286
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and thyroid health in NZ European women

Abstract: The primary aim of the study was to determine differences in the hormonal status (TSH, T3, and T4) between healthy participants and participants with Hashimoto's thyroiditis. The secondary aim of the study was to assess plasma selenium nutritional status and its relationships with the serum levels of thyroid hormones in both of the groups. This study is a pilot and a cross-sectional. Study participants were assigned into two groups, the control group with healthy participants (n=13) and a group of women with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Participants in the study were European women (n=24) who were self-assigned into the healthy control group (n=13) and a group of women with Hashimoto's autoimmune thyroiditis on medication with Levothyroxine (n=11). Both groups presented with the moderate selenium deficiency [30]. It has been suggested that maximal activity of selenoenzyme is reached at blood selenium levels above 1.27 µmol/L, or according to the recent research by Rayman plasma selenium levels in the range of 1.6 to 1.9 µmol/L are considered optimal for thyroid and overall good health [31].Also the study by Karunasinghe et al (2012) have suggested that the basic selenium requirement may vary with genotype for a number of variations in selenoprotein genes, suggesting that an effective dietary selenium intake for one person may be different from that for others.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the study were European women (n=24) who were self-assigned into the healthy control group (n=13) and a group of women with Hashimoto's autoimmune thyroiditis on medication with Levothyroxine (n=11). Both groups presented with the moderate selenium deficiency [30]. It has been suggested that maximal activity of selenoenzyme is reached at blood selenium levels above 1.27 µmol/L, or according to the recent research by Rayman plasma selenium levels in the range of 1.6 to 1.9 µmol/L are considered optimal for thyroid and overall good health [31].Also the study by Karunasinghe et al (2012) have suggested that the basic selenium requirement may vary with genotype for a number of variations in selenoprotein genes, suggesting that an effective dietary selenium intake for one person may be different from that for others.…”
Section: Discussionmentioning
confidence: 99%